Explicit construction of girth-eight QC-LDPC codes and its application in CRT method - Guo-hua ZHANG; Rong SUN; Xin-mei WANG (Tongxin xuebao, 2012)
For arbitrary code lengths of the form PL(P≥3L2/4+L-1),a new family of (4,L)-regular quasi-cyclic (QC) low-density parity-check (LDPC) codes was proposed explicitly with girth ight.Employing the new code as a component code in the construction method of Chinese remainder theorem (CRT),a novel class of compound QC-LDPC codes was presented with both girth at least eight and very flexible code lengths.Simulation results show that the new compound codes with rate 1/2 and moderate code lengths perform very well over the additive white Gaussian noise (AWGN) channel.